Implementation of the Multimedia Development Life Cycle in Making Educational Games About Indonesia - Sodikin Sodikin; Yasin Efendi; Yatimollah Yatimollah (CESS (Journal of Computer Engineering, System and Science), 2023)
Pada materi pembelajaran pengenalan tentang Indonesia, seperti peta, batas-batas wilayah, pembagian waktu dan beragam budaya di Indonesia memerlukan media pembelajaran yang tepat untuk memberikan ilustrasi yang menarik untuk anak-anak Sekolah Dasar. Dalam menjelaskan pengenalan tentang Indonesia masih menerapkan pendekatan yang secara teoritis, seperti penggunaan buku serta papan tulis, yang berakibat pada pelaksanaan pembelajaran yang kurang menarik. Penelitian ini bertujuan untuk mengembangkan game edukasi mengenal Indonesia melalui penerapan pendekatan Multimedia Development Life Cycle (MDLC) yang interaktif dan menarik. Pendekatan MDLC memiliki kemampuan dalam memodelkan serta mengembangkan aplikasi dengan komponen-komponen multimedia didalamnya. Game edukasi ini dibangun berbasis website agar mudah dalam penggunaanya serta aksesnya. Untuk membangun game edukasi yang interkatif dan menarik perlu melibatkan objek-objek yang sesuai dengan sasaran pengguna, seperti penggunaan objek gambar, animasi dan audio yang disesuaikan dengan apa yang disukai oleh pengguna. Berdasarkan hasil pengujian kualitas multimedia interaktif menunjukkan rata-rata responden yang menjawab setuju untuk seluruh pertanyaan adalah 87% dan masuk dalam kategori baik.In introductory learning materials about Indonesia, such as maps, regional boundaries, time divisions, and various cultures in Indonesia, it requires the right learning media to provide interesting illustrations for elementary school children. In explaining the introduction of Indonesia, they still apply a theoretical approach, such as the use of books and blackboards, which results in the implementation of learning that is less interesting. This research aims to develop an educational game about Indonesia through the application of an interactive and interesting Multimedia Development Life Cycle (MDLC) approach. The MDLC approach has the ability to model and develop applications with multimedia components. This educational game is built on a website so that it is easy to use and access. To build educational games that are interactive and interesting, it is necessary to involve objects that are in accordance with the user's goals, such as the use of images, animations, and audio objects that are adjusted to what the user likes. Based on the results of testing the quality of interactive multimedia, it shows that the average respondent who agrees to all questions is 87% and is in the good category.